Refiguring authority : reading, writing, and rewriting in Cervantes - Gerli, E. Michael (University Press of Kentucky, 1995)
In the prologue to Don Quixote, Cervantes maintains that his purpose in writing the work was to undo the pernicious moral and literary example of chivalric romances. Actually, argues E. Michael Gerli in this wide-ranging study, he often did much more. Cervantes and his contemporaries ceaselessly imitated one another - glossing works, dismembering and reconstructing them, writing for and against one another, while playing sophisticated games of literary one-upmanship.
Keywords: Cervantes Saavedra, Miguel de, -- 1547-1616 -- Technique.; Cervantes Saavedra, Miguel de, -- 1547-1616 -- Knowledge -- Literature.; Cervantes Saavedra, Miguel de, -- 1547-1616; Intertextuality.; Rhetoric -- Spain.; Intertextualité.; Rhétorique -- Espagne.; Literature; Intertextuality; Rhetoric; Technique; Spain; Retorica.; Intertekstualiteit.; Electronic book.